(untitled) (Global Journal of Science Frontier Research, 2012)
The epiphytic diversity on avenue trees was assessed in a national highway and two state highways of Udupi district, Karnataka. The study showed that diversity of woody substratum comparatively similar in two state highways and national highway, but recorded high abundance of fast growing, exotic tree varieties in national highways compared to state highways. There is no significant difference between Shannon’s diversity and Pielou’s evenness values between national highway (2.183, 0.878) and state highways (2.304, 0.927). The abundant encountered species are belongs to family Orchidaceae. The native trees with larger girth hold and support more epiphyte species in both national and state highways.